Investigations into the impact of locally modified sensor architectures on the detection efficiency of silicon micro-strip sensors. (5th July 2017) - Poley, L.; Lohwasser, K.; Blue, A.; Benoit, M.; Bloch, I.; Díez, S.; Fadeyev, V.; Gallop, B.; Greenall, A.; Gregor, I.-M.; Keller, J.; Lacasta, C.; et al.
Abstract: The High Luminosity Upgrade of the LHC will require the replacement of the Inner Detector of ATLAS with the Inner Tracker (ITk) in order to cope with higher radiation levels and higher track densities. Prototype silicon strip detector modules are currently developed and their performance is studied in both particle test beams and X-ray beams. In previous test beam measurements of prototype modules, the response of silicon sensors has been studied in detailed scans across individual sensor strips. These scans found instances of sensor strips collecting charge across areas on the sensor deviating from the geometrical width of a sensor strip. The variations have been linked to local features of the sensor architecture. This paper presents results of detailed sensor measurements in both X-ray and particle beams investigating the impact of sensor features (metal pads and p-stops) on the sensor strip response.